Cognitive Linguistic Explorations in Biblical Studies - Howe, Bonnie; Green, Joel B. . (Berlin ; München ; Boston : DE GRUYTER, 2014)
Language and cognition are interconnected, and cognitive linguistics offers methods for analysing how. Here, twelve scholars apply a range of cognitive linguistics methods: conceptual metaphor analysis, cognitive grammar, and the mental space blending and Basic Communicative Spaces Network models. Together, the essays represent ground-breaking and standard-setting work while each raises important interpretive questions for further exploration.
Who Is in Charge?. Mental Space Analysis and Visualization in a Textual Study, Applied to 1 Samuel 28:3-25Cognitive Grammar at Work in Sodom and Gomorrah; 1 John 1:5-10: Conditionals and Performativity; Translating "Thinking" and "Believing" in the Bible. How Cognitive Linguistic Analysis Shows Increasing Subjectivity in Translations; List of Contributors; Author Index; Subject Index.
Keywords: Bible -- Language, style; Cognitive grammar; Bible -- Language, Style; Bible; Religion; RELIGION / Biblical Studies / Bible Study Guides; Electronic books